Comparison the dissipation behaviors and exposure risk of carbendazim and procymidone in greenhouse strawberries under different application method: Individual and joint applications. (30th August 2021) - Di, Shanshan; Wang, Yanhua; Xu, Hao; Wang, Xinquan; Yang, Guiling; Chen, Chen; Yang, Xi; Qian, Yongzhong
Highlights: Joint application of procymidone and carbendazim in strawberry was studied. The dissipation half-lives increased by 1.8 times after joint application. The final residue concentrations increased by 1.8–3.5 times after joint application. There were interactions in the dissipation process of procymidone and carbendazim. The dietary intake risk of procymidone and carbendazim in strawberry was acceptable. Abstract: The dissipation behaviors and exposure risks of individual and joint application of procymidone and carbendazim in greenhouse strawberries were studied. The initial concentrations were similar after individual or joint applications, while the dissipation half-lives and finial concentrations were significantly different. After joint application, the dissipation half-lives of procymidone and carbendazim were 12.9 and 16.0 days, respectively, which were about 1.8 times higher than those after individual application. Furthermore, the final residues under joint application condition were 1.8–3.5 times higher than those under individual application condition. The joint application decreased the dissipation rates of procymidone or carbendazim in strawberries, and increased the final residue concentrations. The dietary intake risks of procymidone and carbendazim (whether applied individually or jointly) were no higher than 0.12, which were acceptable for human health. This work would shed a light for the guidance of the joint application and risk assessment of the typical fungicides in strawberry.